(untitled) (University of Thi-Qar Journal of Science, 2019)
Mobile devices have now surpassed personal computers (PC) in terms of popularity. Smartphones now come withpowerful multi-core processors, loaded with considerable amounts of memory and are capable of carrying out complexoperations with relative ease. However, this increase in technology has meant that it has now become susceptible tosome of the same problems that PC‘s face. In this paper, I will talk about the malware, virus and other security problemsfacing mobile devices and their possible solutions.